Apparatus using cordless attachments (excluding cellular radio apparatus) for connection to analogue interfaces of public switched telephone networks. Specification for the simple call routeing mode of cordless PBX operation with analogue interfaces to the PSTN and terminating stations treated as an entirety Part 3, (15th July 1992) - British Standards Institution,
No abstract available